UNHEALTHY DIET PRACTICES AND ANEMIA IN YOUNG WOMEN - Wahyu Setyaningsih, S.ST, M.Kes; Herawati Mansur; Naimah Naimah (UNIVERSITAS AIRLANGGA, 2022)
Background: Adolescent anemia needs to be the focus of attention because anemia in young women can have an impact on health during pregnancy and childbirth. Meanwhile, many young women practice unhealthy diet for various reasons. This study was conducted to determine the relationship between unhealthy diet practices and anemia status in female high school students in Malang. Method: This study used an observational analytic design with a cross-sectional approach. The research was conducted in 5 public high schools in Malang. The research sample was 188 young women, selected by simple random sampling method. Collecting data using a structured questionnaire and Food Frequency Questionnaire. Data in the form of hemoglobin levels of research subjects were obtained using a digital hemoglobin measuring device. Data analysis was performed by univariate and bivariate (chi-square). Result: This study shows that the incidence of anemia in adolescent girls in Malang is 59.04% and those who practice unhealthy diet are 22.34%. The results of the analysis showed that there was a significant relationship between unhealthy diet practices and anemia status (p-value 0.027). Conclusion: The prevalence of anemia in adolescent girls is still high and more comprehensive efforts are needed to prevent anemia. The strategy for preventing anemia in young women can be done through education related to the consumption of balanced nutrition and the nutritional needs of the body, so as to create awareness of adolescents about their nutritional status and implement a healthy diet. Keywords: Unhealthy Diet, Adolescent Anemia, Young Women